Crystal structure of methyl 3′-benzamido-4′-(4-methoxyphenyl)-1′-methylspiro[indeno[1,2-b]quinoxaline-11,2′-pyrrolidine]-3′-carboxylate - Chandralekha, Kuppan (Acta Crystallogr E Crystallogr Commun, 2016)
In the title compound, C(35)H(30)N(4)O(3), the spiro C atom connects the five-membered pyrrolidine ring and the indenoquinoxaline ring system. The pyrrolidine ring adopts a twist conformation. An intramolecular N—H⋯N interaction between the amino group and the pyrazine ring is observed. In the crystal, molecules are linked by a pairs of C—H⋯O hydrogen bonds, forming inversion dimers.